Empowering Tourism Accessibility: A Digital Revolution in Pieria, Greece - Charisios Achillas; Dimitrios Aidonis; Ioannis Tsampoulatidis; Dimitrios Folinas; Ioannis Kostavelis; Naoum Tsolakis; Dimitrios Triantafyllou; Christos Vlachokostas; Athanasios Kelemis; Vasileios Dimou (Applied Sciences)
Accessibility is a fundamental human right and a key driver for inclusive tourism, particularly for individuals with disabilities, the elderly, and others with mobility challenges. This study aims to promote the Pieria region, Greece, as an “Accessible Tourist Destination” through the development of a digital platform designed to provide detailed information on the accessibility of routes, public spaces, and points of interest. The platform collects and displays data on the region’s accessibility infrastructure, including ramps, sidewalks, and points of cultural and tourist interest, allowing users to plan safe and convenient routes. The methodology involves comprehensive audits of accessibility features, and the data are integrated into an online platform, enabling personalized suggestions for users based on their needs. Initial results from the Platamonas area show detailed documentation of 68 points of interest and 97 routes, improving the accessibility experience for visitors. The findings suggest that accessible tourism has the potential to not only enhance social inclusion, but also contribute to local economic growth by attracting a broader range of visitors. The digital platform represents a significant step towards promoting tourism for all in Pieria.